How Financial Literacy Shapes Impulsive 'Paylater' Buying Among Yogyakarta Students - Hanivah Oktaviana; Seto Satriyo Bayu Aji (Proceeding International Conference on Accounting and Finance, 2025)
This study examines the influence of financial literacy on impulsive buying behavior in students using paylater services at Universitas Aisyiyah Yogyakarta. Through the mixed method, this research used questionnaires and interviews with 120 respondents for the questionnaire and three respondents for the interviews. The results show that gender, financial pressure, and financial literacy significantly influence impulsive buying behavior in shopping. Female students tend to be more impulsive compared to male students. Financial pressure increases the tendency for impulsive buying, while better financial literacy allows students to control impulsive purchases, although less effectively. These findings highlight the importance of financial literacy for students in reducing impulsive buying among students who use paylater services.